Composting Household Organic Waste with A Simple Biocomposter - Wiryawan, I Made Merta; Madrini, da Ayu Gede Bintang; SumiyatI, (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Household waste can be processed into compost. The purpose of this research is to obtain a good mix composition between household waste and rice hulls that produce compost quality according to SNI and determine which biocomposter produces the fastest compost. In order to produce compost, the household waste was added with rice hulls to determine the best material compositionratio and to achieve Indonesian standar in compost material i.e SNI 19-7030-2004. The comparison between household waste and rice hulls for A1, A2, and A3 is (1:0), (1:1) and (1:2) respectively. The composting process was carried out for 60 days and used two different biocomposter models, namely modified biocomposter and old biocomposter. Temperature, pH and water content were measured daily while organic matter, electrical conductivity (EC) and C/N ratio were measured at the beginning of composting and at the end of composting. The results showed that the final temperature and final pH in all bio composters did not show a significant difference. For the best water content produced by treatment A1 (1:0) on each bio composter. The best composition of the mixture produced in the ratio A1 (1:0) because the household waste obtained or the initial raw material has met the C/N ratio of compost raw materials, which is 45.81. All biocomposters have the ability of producing compost within 60 days. All bio composters reached a thermophilic temperature on day 25 and all bio composters run into a decrease in temperature on day 45, due to the addition of water every 7 days during the composting process.